Rancang Bangun Alat Filterasi Limbah Minyak Pelumas (Oli Bekas) Menggunakan Pasir Zeolit, Karbon Altif Dan Membran Keramik - Muhammad Rinaldy Kusnadi; Iwan Nugraha Gusniar; Kardiman Kardiman (Fakultas Teknik UMSU, 2021)
The increasing use of motor vehicles, the greater the amount of engine oil consumption. Engine oil cannot be used continuously due to frictional force on the engine, so engine oil is purified. Unused engine oil can pollute the environment because it is categorized as B3 waste. Used engine oil has a higher metal content than new engine oil. The reduction in metal content can be done by using a filtration column containing zeolite and activated carbon with a filtration column height of 20 cm from each media. Besides filtering also used separation by using a ceramic membrane. In the use of filtration columns filtering used oil using zeolite and activated carbon after that continued using a ceramic membrane, before the used oil is heated at a temperature of 700 C then flowed on the ceramic membrane. In this research, a decrease in levels of aluminum (Al), iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) was obtained.